Discover robotics - Hustad, Douglas (Minneapolis : Lerner Publications, 2017)
"Did you know that robots play a very large role in the lives of humans? Discover the new ways that scientists hope to use robotics in the future in this high-interest book."--
What is robotics? -- Robots in manufacturing -- Robots for personal use -- Robot explorers.
Includes bibliographical references and index.
Ages 8-11.
Grades 4 to 6.
Keywords: Robotics -- Juvenile literature; Personal robotics -- Juvenile literature; Space robotics -- Juvenile literature